Pergeseran Hukum Waris Islam bagi Ahli Waris Non-Muslim: Studi Indonesia dan Malaysia - Andiyah Farodisa; Abd. Rouf (Lembaga Yasin AlSys, 2026)
Although Islamic inheritance law for non-Muslim heirs has received attention in various previous studies, research that specifically discusses shifts in Indonesian jurisprudence and compares them with the Malaysian legal system remains limited. This study aims to analyze the shift in Islamic inheritance law for non-Muslim heirs in Indonesia and compare it with legal regulations in Malaysia. This study used a qualitative approach with a normative legal research design through conceptual, statutory, case, and comparative legal approaches. Data were collected through a literature review of classical Islamic jurisprudence, the Compilation of Islamic Law, Supreme Court decisions, Malaysian regulations, and related literature, and were then analyzed descriptively and analytically. The results show that Indonesia has experienced a shift in legal practice through the jurisprudence of obligatory bequests without positioning non-Muslim heirs as direct heirs. In contrast to Indonesia, Malaysia places greater emphasis on the normative-institutional separation between Muslim and non-Muslim inheritance law. These findings broaden the understanding of the flexibility of Islamic inheritance law in plural societies. The conclusion of this study affirms that obligatory bequests serve as an instrument of family justice in the context of religious differences, although normative strengthening is still needed to ensure legal certainty. The implications of this study provide a theoretical contribution to the development of Islamic inheritance law studies and practical implications for the formulation of Islamic family law policies that are more responsive to the realities of plural societies.